Nutrient intake and nutrition knowledge of lactating women (0-6) months postpartum) in a low socio-economic area in Nairobi, Kenya - Gericke, Gerda J. (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2010.